2016
DOI: 10.1155/2016/1289328
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Randomized Controlled Study of SMS Text Messages for Prevention of Mother-to-Child Transmission of HIV in Rural Kenya

Abstract: Background. Antiretroviral medications are key for prevention of mother-to-child transmission (PMTCT) of HIV, and transmission mitigation is affected by service delivery, adherence, and retention. Methods. We conducted a cluster-randomized controlled study in 26 facilities in Nyanza, Kenya, to determine the efficacy of SMS text messages on PMTCT outcomes. The relative risk and confidence intervals were estimated at the facility level using STATA. Results. 550 women were enrolled, from June 2012 to July 2013. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 13 publications
(15 reference statements)
4
58
0
Order By: Relevance
“…The final study, also conducted in Kenya, offered 3-6 weekly, semi-automated stage-based SMSs, together with airtime, to women to facilitate an increased communication with PMTCT trained CHWs until their final 6-8 postpartum visit. They found no significant difference in either infant HIV testing rates or infant HIV transmission rates with this intervention (Kassaye et al, 2016).…”
Section: Infant Hiv Testing and Infant Transmission Ratesmentioning
confidence: 82%
See 3 more Smart Citations
“…The final study, also conducted in Kenya, offered 3-6 weekly, semi-automated stage-based SMSs, together with airtime, to women to facilitate an increased communication with PMTCT trained CHWs until their final 6-8 postpartum visit. They found no significant difference in either infant HIV testing rates or infant HIV transmission rates with this intervention (Kassaye et al, 2016).…”
Section: Infant Hiv Testing and Infant Transmission Ratesmentioning
confidence: 82%
“…The other study from Kenya assessed the effect of a combining gestation-based PMTCT SMS and increased communication between women and community health workers (CHW) on ART initiation in ANC as well as ART adherence at 34-36 weeks of gestation and delivery. The authors reported no significant difference in either ART initiation or adherence between the intervention arm and the control arm who were allowed to directly communicate with the CHW whenever they needed but did not receive any PMTCT SMSs (Kassaye et al, 2016).…”
Section: Maternal Art Initiation and Art Adherencementioning
confidence: 97%
See 2 more Smart Citations
“…While access to a mobile phone is significantly associated with postpartum retention in PMTCT [42–44], there are few studies evaluating the long-term impact of mobile phone technologies on improving long-term retention and adherence in the context of Option B+. One cluster randomized trial of text messages to support PMTCT care in Kenya did not demonstrate increased uptake of PMTCT services such as ART uptake, facility delivery, or infant testing, but it did not study the effects long term [45]. Another recent randomized trial in Kenya used behavior-based text messaging to improve uptake of early infant diagnosis and postnatal retention [23].…”
Section: Discussionmentioning
confidence: 99%